2005
DOI: 10.1038/sj.onc.1209041
|View full text |Cite
|
Sign up to set email alerts
|

Unshackling the links between reovirus oncolysis, Ras signaling, translational control and cancer

Abstract: Reovirus has an inherent preference for replicating in cells with dysregulated growth factor signaling cascades that comprise Ras activation. Precisely how reovirus exploits the host cell Ras pathway is unclear, but there is evidence suggesting that activated Ras signaling is important for efficient viral protein synthesis. Defining the molecular mechanism of reovirus oncolysis will shed light on reovirus replication and important aspects of cellular transformation, Ras signaling cascades and regulation of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 89 publications
0
75
0
Order By: Relevance
“…8,9,44 The detailed relationship between the cell's Ras status and the various consequences of infection has not been fully elucidated yet. 5,44 While our data suggests components of the Ras/ RalGEF/p38 pathway 6 (particularly p38 and in some cell lines PI3K, but not MEK 1/2) are implicated in the reovirus-induced killing of melanoma (Figure 4), for clinical application the key findings of this study are the sensitivity of melanoma (both cell lines and primary tumours) to reovirus killing and replication, together with the relative resistance of Melan-A normal melanocytes. Sequencing to date of our lines has shown that they are all mutant in the Ras/BRAF pathway (as expected for melanomas 45 ), while Melan-A is normal.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,44 The detailed relationship between the cell's Ras status and the various consequences of infection has not been fully elucidated yet. 5,44 While our data suggests components of the Ras/ RalGEF/p38 pathway 6 (particularly p38 and in some cell lines PI3K, but not MEK 1/2) are implicated in the reovirus-induced killing of melanoma (Figure 4), for clinical application the key findings of this study are the sensitivity of melanoma (both cell lines and primary tumours) to reovirus killing and replication, together with the relative resistance of Melan-A normal melanocytes. Sequencing to date of our lines has shown that they are all mutant in the Ras/BRAF pathway (as expected for melanomas 45 ), while Melan-A is normal.…”
Section: Discussionmentioning
confidence: 99%
“…Reovirus, a naturally occurring benign human pathogen, preferentially targets cancerous cells of many origins and is currently under clinical trials as a novel anticancer therapeutic agent (23,24). Reovirus efficiently destroys local as well as distant metastatic tumors in immunocompromised animals even after a single injection administered through intravenous, intraperitoneal, or intratumoral routes (25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…To date, only wild-type T3D has been used in clinical trials. 1,6,41 The results of this approach are encouraging and the procedure is welltolerated. However, the scarcity or inaccessibility of reovirus receptors on the surface of tumor cells may limit the efficacy of wild-type reoviruses as oncolytic agents.…”
Section: Discussionmentioning
confidence: 92%